Disappearing wetlands - Challand, Helen J. (Chicago : Children's Press, 1992)
Examines the ecological role of wetlands and discusses how they are formed, what life they support, and how people modify or destroy them.
Includes index.
Appraisal-Science Books for Young People.
Book Links (A.L.A.).
School Library Journal.
6.7
5-8
Keywords: Wetland conservation -- Juvenile literature; Wetlands -- Juvenile literature; Wetlands -- North America -- Juvenile literature; Ecology; Wetland ecology; Ecology; Wetland ecology